The Utilization of Seaweed as a Source of Dietary Fiber to Decrease the Serum Cholesterol in Rats - MADE ASTAWAN; TUTIK WRESDIYATI; ANZS BUDY HARTANTA (HAYATI Journal of Biosciences, 2005)
The cholesterol lowering effect of seaweed (Eucheuma cottonii) powder as a source of dietary fiber was evaluated in hypercholesterolemic rats. Four groups of five male Sprague Dawley hypercholesterolemic rats were fed a 0% cholesterol-0% seaweed powder (negative control); 1% cholesterol-5% seaweed powder; 1% cholesterol-10% seaweed powder; and 1% cholesterol-0% seaweed powder (positive control) for 35 days. Seaweed powder contained feed did not affect the growth of rats but significantly lowered the serum total cholesterol, LDL cholesterol, triglyceride, and atherogenic index. The lowest serum cholesterol was found in the hypercholesterolemic rats fed with 1% cholesterol-10% seaweed powder. The values of total-cholesterol, LDL-cholesterol, and triglyceride were 67.7, 33.0, and 47.3 mg/dl, respectively.